Post operative morbidity and 3 years survival rate in diabetic and non diabetic patients undergoing coronary artery bypass grafting in Hospital Universiti Sains Malaysia - Ikhwan Sani, Mohamad (2009)
Diabetes mellitus is a risk factor for development of coronary artery disease and also being linked to worse outcomes after coronary artery bypass grafting (CABG). The purpose of the study is to evaluate the post operative morbidity and survival rate at 3 years following CABG in patients with diabetes mellitus compared to non diabetics. This study was done on 205 patients who underwent elective isolated CABG in Cardiothoracic Uni4 Hospital Universiti Sains Malaysi~ Kubang Kerian from January 2002 to December 2005. Our study group were divided into diabetes and non diabetes. 90 patients (43.9%) were diabetics and 115 (56.1%) were non diabetics. There were 169 (82.4%) male patients and 36 (17.6%) female patients. Patients' age ranged from 39 to 77 years old. The data showed that diabetic patients had poorer ejection fraction (59% vs 62%, p= 0.03) and preoperative renal failure (25.6% vs 16.6%, p=0.02). There were no significant difference in term of other comorbidities between diabetes and non diabetes group , which were hypertension, chronic obstructive airway disease (COAD), smoking status, cerebrovascular accident (CV A), and hyperlipidaemia (HPL). Intraoperative findings showed no significant findings between both groups which include cardiopulmonary bypass (CPB) time, amount of cardioplegia, aortic cross clamped time and number of bypass performed. Post operative outcome revealed that diabetic patients had higher risk of developing harvested site infection (61.1% vs 23.5%, p<O.OOI) and post operative renal failure (27.7% vs 7.8%, p<O.OO I). However, no significant differences were noted in other post operative complications, which were sternal wound infection, pneumonia, post operative bleeding, arrythmias and CV A. During follow up until 3 years post operatively, we found that diabetic patients were more frequently being readmitted due to cardiac causes (42.2% vs 27.8%, p=0.03). No differences in term of reoperation rate and recurrent angina post CABO. OveraJI mortality until 3 years post CABO was 15 patients where 10 patients died within 30 days. We reported that no significant outcome between both groups in term of 30 days mortality and 3 years survival rate. As conclusion, this study supported the evidence that diabetes mellitus were the significant prognostic factors for some post CABO complications especiaJiy harvested site infection and post operative renal failure. However, it is difficult to really determine either the disease contribute to post operative death or not in view of smaJJ overall number of mortality .